2018
DOI: 10.1111/xen.12470
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of decellularized porcine liver matrices crosslinked with different chemical and natural crosslinking agents

Abstract: The natural liver extracellular matrix (ECM) achieved by decellularization holds great potential in the fields of tissue engineering and regenerative medicine. Additionally, the use of crosslinking agents on the ECM to stabilize its ultrastructure and enhance scaffold durability is gaining interest in tissue engineering. The objective of this study was to compare the scaffold properties of porcine liver ECM crosslinked with different agents (glutaraldehyde, genipin, and quercetin) to find the best strategy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…However, in our study, the uncrosslinked matrix received the lowest immunogenicity results in xenogeneic subcutaneous/in-situ transplantation, while all crosslinked groups showed the infiltration of neutrophils/macrophages and the overexpressed TNF-a. It is worth mentioning that, consistent with previously studies, PC-and GP-crosslinked dUECM decreased the immunogenic reactions compared to GA group, exhibited a higher biocompatibility [18,35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in our study, the uncrosslinked matrix received the lowest immunogenicity results in xenogeneic subcutaneous/in-situ transplantation, while all crosslinked groups showed the infiltration of neutrophils/macrophages and the overexpressed TNF-a. It is worth mentioning that, consistent with previously studies, PC-and GP-crosslinked dUECM decreased the immunogenic reactions compared to GA group, exhibited a higher biocompatibility [18,35].…”
Section: Discussionsupporting
confidence: 89%
“…Crosslinked decellularized tissue derived scaffold might suitably improve the mechanical properties and biocompatibility, and reduce immune reaction to promote organ regeneration. However, currently, there are only very few studies evaluated the degreadation and biocompability of crosslinked dECM in vivo [18].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil recruitment to xenografts leads to local tissue destruction by the release of enzymes and reactive oxygen species. In the current issue, Gao et al demonstrated that porcine cytokines, including interleukin (IL)‐6, IL‐1beta, and TNF‐alpha, activate human umbilical vein endothelial cells (HUVECs) and promoted gene transcription, linking porcine gene expression post‐transplant with inflammatory responses . The authors note that the above‐mentioned cytokines and their receptors are sufficiently homologous between pig and human to a significant factor.…”
Section: Basic Researchmentioning
confidence: 98%
“…The extensive exploitation of pig livers is associated with both their broad accessibility, as well for the dimensions within a range consistent with the size of human liver. For these reasons, several studies organizations have investigated their application for liver bioengineering [71][72][73].…”
Section: Large Animal Modelmentioning
confidence: 99%